Conservative management of postmenopausal woman with prolonged use of the dislocated intrauterine device which was also unnoticed while hysterectomy - Uçar, Mustafa Gazi; Çakır, Tansel; İlhan, Tolgay Tuyan; Çelik, Çetin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The objectives of this study are to identify and compare the treatment options of woman with uterine perforation caused by intrauterine device (IUD). A 74-years-old woman presented with irritable voiding symptoms and a dislocated IUD into the peritoneal cavity was discovered incidentally during radiologic imaging. While a Lippes loop IUD had been inserted 35 years previously, she had a history of hysterectomy 10 years after an IUD insertion. Not only the patient had forgotten the presence of the IUD, but also it was unnoticed during hysterectomy. Patient has remained asymptomatic for over the 25 years, with the prolonged use of dislocated IUD. The patient managed conservatively and no need for surgical intervention. Once a gynaecologist is faced with the dilemma of whether it is necessary to remove a dislocated IUD or not, patients should undergo an individualized management, balancing both risks and benefits of surgical intervention. Asymptomatic elderly patients with comorbidities may benefit from conservative management with close monitoring.